Re-thinking the Global Age as Interdependence, Opacity and Inertia - Oriol Poveda Guillén; Jakob Svensson (tripleC: Communication, Capitalism & Critique)
In this theoretical essay we criticize theories of modernity and explore the possibility that the modern epoch is coming to a close while a new configuration is emerging: the global age. Building upon sociologist Martin Albrow’s work The Global Age, we claim that Albrow’s scholarship did a remarkable job at outlining the shift away from modernity, but that greater clarity is needed in laying out the main characteristics of the global age. With this essay we aim to fill that gap. Acknowledging that capitalism is the most important feature of our societies, we outline the contours of the global age through three interrelated concepts: interdependence, opacity and inertia which in turn we exemplify with the global environmental crisis, the global economy and the Internet.